Volatile biomarkers non-invasive diagnosis in physiology and medicine - Amann, A. 1956-; Smith, David (Chemical physicist) (Elsevier, 2013)
Volatile organic compounds (VOCs) in exhaled breath, sweat or urine carry much information on the state of human health. The role of VOCs in clinical diagnosis and therapeutic monitoring is expected to become increasingly significant due to recent advances in the field. Volatile Biomarkers: Non-Invasive Diagnosis in Physiology and Medicine includes the latest discoveries and applications for VOCs from the world's foremost scientists and clinicians working in this emerging analytic area. - Appeals to a multidisciplinary audience, including scientists, researchers, and clinicians with an interest in breath analysis - Features the latest scientific research and technical breakthroughs in the diagnostic and therapeutic aspects of volatile organic compounds - Includes case presentations documenting applications in multiple areas of human health and safety.